Hypersensitivity reactions to the Sabin vaccine in children with cow’s milk allergy - Parisi, Claudio Alberto Salvador (2013)
Background: The Sabin vaccine is used worldwide, and most children with food allergies receive it without incident. However, in the 2009 vaccination campaign conducted in Argentina, four children experienced immediate-type hypersensitivity reactions following vaccination. Objective: We aimed to review the medical history of the affected children, study their allergic condition after the episodes and analyse the presence of allergenic vaccine components. Methods: Patients were selected based on their immediate allergic reactions following vaccination. They were assessed for allergies to cow’s milk and hen’s egg. The presence of cow’s milk proteins in the vaccine was tested by various immunoassays involving cow’s milk- or α-lactalbumin-specific polyclonal rabbit antiserum, and patient sera. Results: All of the patients had a history of milk allergy, and no history or current evidence of egg hypersensitivity was found. Levels of cow’s milk- and Sabin vaccinespecific IgE were increased, and the result of a skin prick test with cow’s milk proteins or the Sabin vaccine was positive in each patient. In addition, an ELISA using specific rabbit antiserum detected α-lactalbumin in the Sabin vaccine. When α-lactalbumin was employed as a soluble inhibitor in a competitive ELISA, binding to vaccine-coated plates by cow’s milk- or α-lactalbumin-specific rabbit antiserum or by patient serum containing IgE was inhibited. Conclusions: We have demonstrated that these patients were allergic to cow’s milk, and had circulating and mast cell-bound IgE antibodies specific to cow’s milk proteins. We found that the Sabin vaccine contained α-lactalbumin, which may have been responsible for the reactions elicited following vaccination with the Sabin and dual viral vaccines in combination.